Pengaruh Model Pembelajaran Kooperatif Dan Gaya Kognitif Terhadap Hasil Belajar Sejarah Setelah Mengontrol Kemampuan Awal Siswa - Bambang Gulyanto; Harun Sitompul; Abdul Hasan Saragih (Universitas Negeri Medan, 2021)
This study aims to determine the effect of cooperative learning models and cognitive styles on historical learning outcomes after controlling for students' initial abilities. This research was conducted at SMA Negeri 1 Kisaran and SMA Negeri 2 Kisaran in Asahan Regency in the even semester of the 2020/2021 academic year. This study used a quasi-experimental method with a 2x2 treatment by level design. The sample of this research was 72 people who were taken by using cluster random sampling technique. The data analysis technique used was covariance analysis (ANAKOVA). The results showed that (1) The results of the history learning of the group of students who were taught with the GI model were higher than the group of students taught with the STAD model after controlling for students' initial abilities; (2) The learning outcomes of students who have a FI cognitive style are higher than students who have FD cognitive styles after controlling for students 'initial abilities, (3) There is an interaction effect between cooperative learning models and cognitive styles on historical learning outcomes after controlling for students' initial abilities, (4) The results of learning history between groups of students taught with the GI learning model were higher than the groups of students taught with the STAD model in students who had FI cognitive styles, (5) The results of learning history between groups of students taught with the STAD learning model were more higher compared to the group of students who were taught with the GI learning model, in students who had FD cognitive style after controlling for students' initial abilities.